1963
DOI: 10.1002/aic.690090406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of packing on a fluidized bed

Abstract: A study has been made of the effect of fixed packing on the properties of a gas-fluidized bed, including minimum fluidization velocity, pressure drop, and bed expansion. Experiments using a range of glass beads as fluidizing solid with smooth uniform spheres as packing indicate that both packing size and the ratio of particle to packing diameter are the main variables in correlating the results. Other solids of varying density and shape have also been used. In addition to smooth spherical packing, rough sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

1964
1964
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 3 publications
4
26
0
Order By: Relevance
“…G,,jfp was found to be independent of the initial bed height and $ ratio, but less than that of the same fluidized bed without packing. Similar observations had been made by Sutherland et al (1963) for gas-solid systems packed with solid spheres and Ravindrapandian et al (1980) for liquidsolid systems. This indicates that only a fraction of the total voidage is available for liquid flow.…”
Section: Resultssupporting
confidence: 86%
“…G,,jfp was found to be independent of the initial bed height and $ ratio, but less than that of the same fluidized bed without packing. Similar observations had been made by Sutherland et al (1963) for gas-solid systems packed with solid spheres and Ravindrapandian et al (1980) for liquidsolid systems. This indicates that only a fraction of the total voidage is available for liquid flow.…”
Section: Resultssupporting
confidence: 86%
“…The challenge of limited mass transfer between the bubble and emulsion phases can be addressed by means of using confined fluidized beds, i.e., inserting inert spheres of a size size much larger than the bed material to break down the bubble-emulsion flow structure. It has been shown that doing so provides smooth fluidization and increases bed expansion [3,4]. This will also have other effects that can be beneficial to mass transfer, such as locally increased relative gas-particle velocity.…”
mentioning
confidence: 99%
“…4), which was also formulated in the paper.  As results from the experiments, the confined fluidized systems in spite of geometrical condition d f /D p < 0.096 (Sutherland et al, 1963) should also satisfy the formulated condition ε p /ε p rel < 2.5 (cf. Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Values of  mf rel / ba are up to 10% higher than those obtained in direct measurements within the range of high  p / p rel values. In various papers, the value of d f /D p < 0.096-0.414 (Sutherland et al, 1963) is considered as a boundary condition fluidization of fine particles in a fixed bed. Difficulties related with fluidization of fines from A group Geldart's classification, where extensive development of external surface precludes obtaining uniform fluidization like in case of conventional fluidized bed (Donsi et al, 1990;Zabierowski, 2008), was also mentioned.…”
Section: Minimum Of Fluidizationmentioning
confidence: 99%